(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
The purpose of the research is to test the impact of knowledge management on empowering human resources in the Directorate of Youth and Sports in Dhi Qar. The research relied on the questionnaire as a main tool for collecting the necessary data needed to achieve the objectives of the research. The research community consisted of all managers working in the Directorate of Youth and Sports in Dhi Qar. The sample was taken. Randomly, (123) questionnaires were distributed to determine the level of application of organizational practices in the surveyed directorate, and (118) questionnaires were retrieved from them. The descriptive analysis method was also adopted, through the use of (SPSS V.28) program in analyzing the research data to answer questions and test hypotheses. search. The results of the research found that there is a statistically significant effect between knowledge management and its combined dimensions and the empowerment of human resources in the Youth and Sports Directorate in Dhi Qar. The research recommends the need for the directorate to continue activating the dimensions of human resources empowerment to give administrative and organizational staff the freedom to act and make decisions regarding their work.